Victimological Prevention of Crimes in the Field of Physical Culture and Sports - Oleksii Lytvynov; Anastasia Dzhuzha; Hanna Spitsyna; Dmytro Tychyna (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2021)
The purpose of the article is to analyze the victimological prevention of crimes in the field of physical culture and sports. The authors of the article have carried out a general analysis of victimological prevention of crimes. The authors have defined the list of crimes, the commission of which directly resulted in physical, material or moral damage to athletes, dividing them into crimes: the victims of which are exclusively athletes and the victims of which are both ordinary citizens and athletes. Based on the motivation, the authors have accomplished the classification of athletes who have become victims of criminal encroachments and have offered the directions of victimological prevention of crimes in this sphere. It should be noted that general victimological prevention measures are aimed at identifying victimogenic factors and taking measures to eliminate or neutralize them, i.e. to identify the reasons and conditions of becoming a victim related to protecting the interests of potential victims in general, and to eliminate the causes of their victimization. In general, the problem of protecting the rights and legitimate interests of victims of crimes, effective restoration of their rights, compensation for damage caused by crime, which has been studied since the mid-90s of the last century in connection with the growth rate of crime, remains unresolved, in particular, in the field of physical culture and sports.Keywords: Victimology; Victimological Prevention of Crimes; A Victim; A Sphere of Physical Culture and Sports Pencegahan Viktimologis Kejahatan Di Bidang Kebudayaan Jasmani dan Olahraga AbstrakTujuan dari artikel ini adalah untuk menganalisis pencegahan viktimologis kejahatan di bidang budaya fisik dan olahraga. Penulis artikel telah melakukan analisis umum pencegahan viktimologis kejahatan. Para penulis telah mendefinisikan daftar kejahatan, yang komisinya secara langsung merusak fisik, material, atau moral atlet, membaginya menjadi kejahatan: korbannya adalah atlet eksklusif dan korbannya adalah warga negara biasa dan atlet. Berdasarkan motivasi, penulis telah menyelesaikan klasifikasi atlet yang telah menjadi korban perambahan kriminal dan telah menawarkan arahan pencegahan viktimologis kejahatan di bidang ini. Perlu dicatat bahwa tindakan pencegahan viktimologis secara umum adalah dengan mengidentifikasi faktor-faktor viktimogenik dan mengambil tindakan untuk menghilangkan atau menetralisir, yaitu untuk mengidentifikasi alasan dan kondisi menjadi korban terkait dengan melindungi kepentingan calon korban secara umum, dan untuk menghilangkan penyebab dari viktimisasi mereka. Secara umum, masalah perlindungan hak dan kepentingan sah para korban kejahatan, pemulihan hak-hak mereka secara efektif, kompensasi atas kerusakan yang disebabkan oleh kejahatan, yang telah dipelajari sejak pertengahan 90-an abad terakhir sehubungan dengan tingkat pertumbuhan kejahatan. Kejahatan, masih belum terselesaikan, khususnya, di bidang budaya fisik dan olahraga.Kata Kunci: Viktimologi; Pencegahan Viktimologis Kejahatan; Korban; Bidang Budaya Fisik Dan Olahraga Виктимологическая профилактика преступлений В Области Физической Культуры И Спорта АннотацияЦелью статьи является анализ виктимологической профилактики преступлений в сфере физической культуры и спорта. В статье проведен общий анализ виктимологической профилактики преступлений. Авторами определен перечень преступлений, совершение которых напрямую повлекло за собой физический, материальный или моральный ущерб спортсменам, разделив их на преступления, жертвами которых являются: 1) исключительно спортсмены; 2) как обычные граждане, так и спортсмены. На основе мотивации проведена классификация спортсменов, ставших жертвами преступных посягательств, и предложены направления виктимологической профилактики преступлений в этой сфере. Отмечается, что общие меры виктимологической профилактики направлены на выявление виктимогенных факторов и принятие мер по их устранению или нейтрализации, то есть выявление причин и условий, связанных с защитой интересов потенциальных жертв в целом, и устранение причины их виктимизации. В целом проблема защиты прав и законных интересов потерпевших от преступлений, эффективного восстановления их прав, возмещения ущерба, причиненного преступлением, изучается с середины 90-х годов прошлого века в связи с ростом преступности, в частности, и в сфере физической культуры и спорта.Ключевые слова: виктимология; виктимологическая профилактика преступлений; жертва; сфера физической культуры и спорта.